Impact of the southern annular mode on extreme changes in indian rainfall during the early 1990s - Pao-Wei Huang (Nature Portfolio, 2021)
Abstract The variability in rainfall amounts in India draws much attention because it strongly influences the country’s ecological and social systems. Indian rainfall is associated with climate factors, including El Niño/Southern Oscillation and the Indian Ocean Dipole. Here we identified the Southern Annular Mode (SAM), the primary pattern of climate variability in the Southern Hemisphere, as the ultimate forcing leading to decadal changes in Indian rainfall. Through statistical analyses using observational data covering the period from 1979 to 2015, we show an increase in the decadal rainfall amount in the early 1990s over the Indian region. Examining atmospheric environmental conditions, we demonstrate that conditions have become more favorable over the past few decades. Specifically, during the positive SAM phase since the early 1990s, changes in the atmospheric fields have evoked anomalous vertical motion over the continent and the Indian Ocean, enhancing the southerly cross-equatorial flow by increased land–sea thermal contrast, thereby increasing decadal rainfall in the region.